Chemicals Constituents Isolated from Cultivate Alpinia conchigera Griff. and Antimicrobial Activity - Mohamad Taib, Mohamad Nurul Azmi; Anuar, Nursyazwani; Mohd Hanafiah, Khayriyyah; Al-Shammary, Aeman Ali Kudayr; Saaid, Mardiana; Awang, Khalijah (Penerbit Universiti Sains Malaysia, 2020)
Alpinia conchigera Griff. is a plant species from the family Zingiberaceae. Coloquially known as wild ginger, Alpinia conchigera Griff. is used as food condiment and for traditional treatment of skin diseases. Isolation studies to identify bioactive compounds of rhizomes of Alpinia conchigera yielded seven compounds; 1‘S-1'-acetoxychavicol acetate (1), trans-p-coumaryl diacetate (2), p-hydroxycinnamyl acetate (3), 1‘S-1'-hydroxychavicol acetate (4) p-hydroxybenzaldehyde (5), stigmasterol (6) and β-sitosterol (7). Compounds 1, 2 and 5 were evaluated for antimicrobial activity against methicillin-resistant Staphylococcus aureus (MRSA). Among the compounds tested, Compound 1 showed good antimicrobial activity against the strain of MRSA with minimum inhibition concentration (MIC) value of 0.5 mg/mL. Meanwhile, Compounds 2 and 5 exhibited moderate activity with MIC value between 1.0 and 2.0 mg/mL. These findings indicate antimicrobial potential of 1‘S-1'- acetoxychavicol acetate (1), compound derived from rhizome of Alpinia conchigera Griff. against MRSA, which warrant further investigation. © Penerbit Universiti Sains Malaysia, 2020.